Exergy Analysis of the Revolving Vane Compressed Air Engine - Alison Subiantoro; Kin Keong Wong; Kim Tiow Ooi (International Journal of Rotating Machinery)
Exergy analysis was applied to a revolving vane compressed air engine. The engine had a swept volume of 30 cm3. At the benchmark conditions, the suction pressure was 8 bar, the discharge pressure was 1 bar, and the operating speed was 3,000 rev·min−1. It was found that the engine had a second-law efficiency of 29.6% at the benchmark conditions. The contributors of exergy loss were friction (49%), throttling (38%), heat transfer (12%), and fluid mixing (1%). A parametric study was also conducted. The parameters to be examined were suction reservoir pressure (4 to 12 bar), operating speed (2,400 to 3,600 rev·min−1), and rotational cylinder inertia (0.94 to 2.81 g·mm2). The study found that a higher suction reservoir pressure initially increased the second-law efficiency but then plateaued at about 30%. With a higher operating speed and a higher cylinder inertia, second-law efficiency decreased. As compared to suction pressure and operating speed, cylinder inertia is the most practical and significant to be modified.